Preparation and X-ray Structural Study of 1-Arylbenziodoxolones; The Journal of Organic Chemistry; Vol. 78, iss. 8 - Yusubov M. S. Mekhman Suleiman-Ogly (Suleimanovich); Yusubova R. Ya. Roza Yavidovna; Nemykin V. N.; Zhdankin V. V. Viktor Vladimirovich (2013, 2013)
Title screen